2020
DOI: 10.5137/1019-5149.jtn.29021-20.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of lumbar arteries and relationship with intervertebral discs\', a study of surgical anatomy on human fresh cadavers..

Abstract: AIM: To examine the morphological structure of anterior lumbar spinal region. MATERIAL and METHODS: Fifteen fresh human cadavers were studied in our forensic medicine institution. Within the first 24 hours after death, cadavers were subject to a routine autopsy, by which the intestines were removed and the structures adjacent to the lumbar arteries (LAs) were examined. The following characteristics of the LA were examined and recorded: diameter, number of LA, intervertebral disc, and vertebral corpus relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There are a lot of studies discussing vascular injury in spine surgery. Vascular complications can occur with an incidence of 1–5 in 10,000 disc operations, they most commonly appear at the L4/L5 level, result in arteriovenous fistulas and predominantly concern injury of common iliac artery, aorta or lumbar arteries [ 5 , 22 ]. Majority of works discuss that problem only in anterior approach procedures [ 5 , 7 , 9 , 15 , 18 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of studies discussing vascular injury in spine surgery. Vascular complications can occur with an incidence of 1–5 in 10,000 disc operations, they most commonly appear at the L4/L5 level, result in arteriovenous fistulas and predominantly concern injury of common iliac artery, aorta or lumbar arteries [ 5 , 22 ]. Majority of works discuss that problem only in anterior approach procedures [ 5 , 7 , 9 , 15 , 18 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular complications can occur with an incidence of 1–5 in 10,000 disc operations, they most commonly appear at the L4/L5 level, result in arteriovenous fistulas and predominantly concern injury of common iliac artery, aorta or lumbar arteries [ 5 , 22 ]. Majority of works discuss that problem only in anterior approach procedures [ 5 , 7 , 9 , 15 , 18 , 31 ]. Nowadays, the posterior approach is considered to minimalize the chance of vascular injury, but it still does not eliminate it—more often it provides long-term complications which can be challenging to diagnose [ 14 , 19 , 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fifth lumbar arteries from our study originated directly from the aorta with 50% arising as one common stem and branching into two, while 50% arose singly. Most previous studies have reported that the fifth lumbar arteries originate from the middle sacral artery or the aorta (2,14,16,17). This may be due to the embryological development of the intersegmental branches of the dorsal aorta in the fetus.…”
Section: Pattern Of Origin Of Fifth Lumbar Arteriesmentioning
confidence: 99%